Desenvolvimento e aplicação de um gerador síncrono virtual para o controle de inversores na geração distribuída - Carletti, Daniel (2015)
The exponential growth of the market share of renewable energy sources (RES), together with the increase in the number of distributed generation units (DG) installed, for example modular photovoltaic panels, fuel cell, among others, can lead to an unstable and unsecure power system in the future due to the reduction of the total rotational inertia in the system. In order to solve this problem, a solution using the control of power inverters that interface RES to the grid is becoming popular. A way to stabilize the grid is to add a virtual rotational inertia to DGs. For that, it is necessary to combine a short-term energy storage system with a suitable control mechanism for the DG power electronics converter. In this way a generator can behave like a "Virtual Synchronous Generator" (VSG) and contribute to stabilization of grid frequency. In this Master’s thesis, all the mathematical development for the control of a VSG is presented. A system is proposed to simulate both VSG and the synchronous generator in order to prove their dynamic behaviors equivalence under a number of grid transients. The simulation results will be discussed to validate this equivalence. In the end, a real application of the virtual machine will be proposed. The conncetion of a solar array to the grid using a VSG as the power converter interface will be verified using a simulation of a real power system.